The Existence of Customary Law in Managing Fishery Resources in Indonesia - Radityani, Fitri; Utami, Aulia Rahmi; Oktavia, Sella; Wati, Kiran Lavanya; Muzahidi, Muzi; Nurasiyah, Siti (MAIYAH, 2024)
The diversity of cultures and customary laws in Indonesia is reflected in the management of fisheries resources. This article explores various customary laws that are still valid in several regions in Indonesia, such as Sasi customary law in Maluku, Laot customary law and the Panglima laot institution in Aceh, Awig-awig customary law in Lombok, Masa ombo customary law in Central Sulawesi, customary law Lubuk ban in Jambi, Lilifuk customary law in NTT, and the Bapongka cultural system in the Bajo tribe. Through descriptive and qualitative research, this article highlights the implementation, changes and challenges faced by customary law in the face of modernization and globalization. It was found that this customary law not only functions to manage fisheries resources sustainably, but also plays an important role in maintaining local wisdom, traditional values, and the welfare of local communities. This research emphasizes the importance of understanding and respecting customary law in efforts to preserve natural resources and local culture in Indonesia.